2013
DOI: 10.1590/s0102-09352013000200030
|View full text |Cite
|
Sign up to set email alerts
|

Substituição de minerais inorgânicos por orgânicos na alimentação de poedeiras semipesadas

Abstract: RESUMOAvaliou-se o efeito da suplementação dietética de fontes orgânicas de microminerais para galinhas poedeiras sobre o desempenho e a qualidade do ovo. Foram utilizadas 216 aves de linhagem comercial, distribuídas num delineamento inteiramente ao acaso, com quatro tratamentos e nove repetições, com seis aves por parcela. O experimento teve duração de 140 dias, divididos em cinco ciclos de 28 dias. Os tratamentos consistiram de uma dieta basal formulada para atender às exigências nutricionais das aves, suple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
1
3
0
1
Order By: Relevance
“…Lesson and Summers (2005) mentioned methionine among the possible nutrients that can be adjusted to manipulate egg weight. An increase in egg weight was also observed by Figueiredo Júnior et al (2013) at the lowest levels of inclusion of organic minerals in relation to the inclusion of inorganic minerals; and…”
Section: Organic Copper…supporting
confidence: 55%
See 1 more Smart Citation
“…Lesson and Summers (2005) mentioned methionine among the possible nutrients that can be adjusted to manipulate egg weight. An increase in egg weight was also observed by Figueiredo Júnior et al (2013) at the lowest levels of inclusion of organic minerals in relation to the inclusion of inorganic minerals; and…”
Section: Organic Copper…supporting
confidence: 55%
“…Figueiredo Júnior et al (2013) tested decreasing levels of organic minerals (66 and 33%) and observed an improvement in production with the supplementation of 6.6mg/kg Cu, 26.4mg/kg Fe, 52.8mg/kg Mn and 36mg/kg Zn. However, in their study, birds fed diets with the inclusion of 3.3mg/kg Cu, 13.2mg/kg Fe, 26.4mg/kg Mn and 18mg/kg Zn (similar concentrations to present in the OM35 treatment) exhibited similar parameters to those shown by the birds fed the inorganic premix.…”
Section: Organic Copper…mentioning
confidence: 99%
“…Experimental results using organic minerals in diets for laying hens are controversial. Similar studies have shown no differences in the productive performance of commercial laying hens receiving diets with organic minerals compared to birds receiving diets supplemented with inorganic minerals (;Figueiredo et al, 2013;Carvalho et al, 2015). The substitution of inorganic by organic minerals in diets for laying hens improved egg mass, feed conversion to egg mass, and feed conversion per dozen eggs when 66% and 100% of inorganic minerals was replaced by organic minerals in the diet (Gheisari et al, 2011).…”
Section: Resultsmentioning
confidence: 71%
“…Alves et al (2015) only observed effects of organic minerals in diets for laying hens on the variable shell thickness, where they obtained better results; an effect of mineral type on the specific gravity of the eggs was not observed. Figueiredo et al (2013) observed that the substitution of inorganic by organic minerals in diets for laying hens provided better specific gravity and shell thickness when 66% and 100% of inorganic minerals was replaced by organic minerals.…”
Section: Resultsmentioning
confidence: 99%
“…Em um estudo que abrangeu vários estados brasileiros, Favero et al (2002) relataram prevalência média nacional de 17,7%, 29% e 24,5% de soropositivos para caninos, equinos e suínos, respectivamente. No Brasil, conforme Langoni et al (1995), a leptospirose em suínos já foi uma das principais causas de falhas reprodutivas em vários estados, principalmente nas regiões Sul e Sudeste do País, situação que se perpetua ainda hoje (FIGUEIREDO JÚNIOR et al, 2013). De acordo com as normas para certificação de granjas de reprodutores suídeos (GRSC), " [...] toda granja certificada deverá ser livre de peste suína clássica, doença de Aujeszky, brucelose, tuberculose, sarna e livre ou controlada para leptospirose" (MAPA, 2002).…”
Section: Introductionunclassified